Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Quick algebra 1 question for 10 points!

Only answer if you know the answer, quick shout-out to tariqareesha2 and MrBrainly, tysm for the help!


Quick Algebra 1 Question For 10 Points Only Answer If You Know The Answer Quick Shoutout To Tariqareesha2 And MrBrainly Tysm For The Help class=

Sagot :

Answer:

B {3/2, -5/3}

Step-by-step explanation:

6x² + x - 15 = 0

6x² + 10x - 9x - 15 = 0

2x(3x + 5) - 3(3x + 5) = 0

(3x + 5)(2x - 3) = 0

3x + 5 = 0  or  2x - 3 = 0

3x = -5  or  2x = 3

x = -5/3  or  x = 3/2

Answer: B {3/2, -5/3}

Esther

Answer:

[tex]\left\{\dfrac{3}{2},\ -\dfrac{5}{3}\right\}[/tex]

Step-by-step explanation:

Given quadratic equation: [tex]6x^2+x-15=0[/tex]

[tex]\implies a=\textsf{6},b=\textsf{1},c=\textsf{-15}[/tex]

..................................................................................................................................................

[tex]{\large \textsf{ Quadratic Formula: }}x=\dfrac{-b\pm \sqrt{b^2-4ac}}{2a}\ \Bigg{\|}\ \textsf{when }ax^2+bx+c=0[/tex]

..................................................................................................................................................

Step 1: Substitute the given values into the formula and simplify.

[tex]\implies x=\dfrac{-{(\textsf1})\pm \sqrt{\textsf{(1)}^2-4(\textsf{6}){(\textsf{-15})}}}{2{(\textsf{6})}}[/tex]

[tex]\implies x=\dfrac{-1\pm \sqrt{1-4(-90)}}{12}[/tex]

[tex]\implies x=\dfrac{-1\pm \sqrt{1+360}}{12}[/tex]

[tex]\implies x=\dfrac{-1\pm \sqrt{361}}{12}[/tex]

[tex]\implies x=\dfrac{-1\pm 19}{12}[/tex]

Step 2: Separate into two cases.

[tex]x_1=\dfrac{-1+19}{2}[/tex]

[tex]x_2=\dfrac{-1-19}{2}[/tex]

Step 3: Solve both cases.

[tex]\implies x_1=\dfrac{-1+19}{12}=\dfrac{18}{12}=\dfrac{6\times3}{6\times2}=\boxed{\dfrac{3}{2}}[/tex]

[tex]\implies x_2=\dfrac{-1-19}{12}=\dfrac{-20}{12}=\dfrac{-4\times5}{4\times3}=\boxed{-\dfrac{5}{3}}[/tex]

The solutions to this quadratic are: [tex]x_1=\dfrac{3}{2},\ x_2=-\dfrac{5}{3}[/tex]

..................................................................................................................................................

Learn more about quadratic equations here:

https://brainly.com/question/28123532

https://brainly.com/question/28063094

We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.